SVIP is a molecular determinant of lysosomal dynamic stability, neurodegeneration and lifespan - Alyssa E. Johnson (Nature Portfolio, 2021)
Valosin-Containing Protein (VCP) is linked to diverse degenerative diseases. Here, the authors show that Small VCP Interacting Protein (SVIP) recruits VCP to lysosomes, with gain and loss of SVIP muscle expression modifying neural degeneration, animal behaviour and lifespan.